Concepção e implementação de um scanner 3D para ensino e aprendizagem . - Alencar, Francisco Alexandre Ribeiro de (2010)
The three-dimensional scanning is one of the major challenges in computer graphics (CG). This subject covers knowledge of the areas of computer vision, image processing, geometric modeling, visualization and sensor development. Three-dimensional reconstruction has many applications in different areas like Engineering, Archeology, Heritage, Architecture, Education, Arts, Medicine and Industrial Design among others. To be able to perform properly scanning a surface allowing the three-dimensional reconstruction is needed basically three steps: acquisition of elevation data of surface processing such data and surface reconstruction on the accuracy specified. This process, although interesting, has proved difficult to ownership in the process of teaching and learning of computer graphics. Considering that direct contact with concrete representations, according to the literature, facilitates learning the development of this work was the starting point to show a simplified technique for producing a three-dimensional scanner based on free software in order to motivate and facilitate the learning of concepts in the field of computer graphics.